Characteristics of calcium derived from Pinctada maxima shells at different calcination temperatures as a candidate material for water quality control - Susi Rahayu; Arif Budianto; Sri Anum; Hurnah Hurnah; Dian Wijaya Kurniawidi (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2026)
Pearl oyster (Pinctada maxima) aquaculture is a major economic activity in coastal regions of Indonesia, particularly in Lombok, West Nusa Tenggara, but generates substantial shell waste that remains underutilized. These shells are rich in biogenic calcium carbonate (CaCO₃), offering strong potential as a sustainable raw material for calcium oxide (CaO) production. This study investigates the effect of calcination temperature on the characteristics of calcium-based materials derived from P. maxima shells and evaluates their suitability as candidate materials for water quality control. Shell powders were calcined at 500 °C, 600 °C, and 700 °C for 5 h, producing samples labeled CC500, CC600, and CC700. The resulting materials were characterized through organoleptic analysis, acid–base titration, and X-ray diffraction (XRD) to assess physical properties, residual CaCO₃ content, crystalline phases, and microstructural parameters. The results showed that increasing calcination temperature significantly influenced material characteristics. CC700 exhibited a lighter color, finer and more homogeneous texture, and the lowest CaCO₃ content (68.74%), indicating more effective thermal decomposition. XRD analysis revealed dominant calcite phases in all samples, with decreasing aragonite intensity and reduced crystallinity (35.81%) at higher temperature, accompanied by increased crystal size and microstrain. These findings demonstrate that controlled calcination temperature is a critical factor governing CaCO₃ decomposition and structural evolution in P. maxima shell-derived materials. Calcination at approximately 700 °C represents an effective threshold for producing CaO with physicochemical characteristics favorable for water quality control applications in fisheries and aquaculture. The study provides baseline data supporting the sustainable valorization of pearl oyster shell waste within circular economy frameworks.